2020
DOI: 10.1039/d0md00009d
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships of sulfonamides derived from carvacrol and their potential for the treatment of Alzheimer's disease

Abstract: We investigated the potential of sulfonamides derived from carvacrol as candidates for treatment of Alzheimer's disease. The results are very promising for the molecular target investigated as well as for the phenotypic assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This is an important measure to check for possible false positives in pain studies, as these parameters can be easily confused with an analgesic effect of the evaluated drug and cause research bias. Thus, to examine the activity of the carvacrol derivatives on spontaneous locomotion, the open-field test was performed as described above ( Nucci-Martins et al, 2016 ; de Souza et al, 2020 ). The open-field test device was a wooden box (40 × 60 × 50 cm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important measure to check for possible false positives in pain studies, as these parameters can be easily confused with an analgesic effect of the evaluated drug and cause research bias. Thus, to examine the activity of the carvacrol derivatives on spontaneous locomotion, the open-field test was performed as described above ( Nucci-Martins et al, 2016 ; de Souza et al, 2020 ). The open-field test device was a wooden box (40 × 60 × 50 cm).…”
Section: Methodsmentioning
confidence: 99%
“… Melo et al (2010) demonstrated that doses of 12.5, 25, and 50 mg/kg of carvacrol, administered orally, have an anxiolytic effect and do not alter the locomotor activity of the animals. In a previous study, we demonstrated that some synthetic sulfonamides derived from carvacrol at a dose of 30 mg/kg, intraperitoneal (ip), are able to reduce streptozotocin-induced Alzheimer’s disease deficits, in addition to producing anxiolytic and antioxidant effects, without affecting locomotor activity of animals ( de Souza et al, 2020 ). Also, it was confirmed that carvacrol, administered orally, at single doses of 50 and 100 mg/kg, produces significant inhibition of nociception caused by chemical (formalin and acetic acid) and thermal stimulations (hot-plate test) ( Cavalcante Melo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvacrol elevates vascular inflammation [ 35 ] and it is also cardioprotective [ 36 ]. Additionally, it has behavioural calming effects, most likely via inhibition of gut-brain axes [ 16 ], it is neuroprotective [ 37 ], alleviating neurodegeneration and depressive-like behaviours [ 30 ], and is considered for treatment of Alzheimer's disease [ 38 ]. Recently, carvacrol's known antiviral activity was in the spotlight again, with suggestions that it is a respectable candidate for the development of anti-COVID-19 drugs [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carvacryl derivatives, either natural or synthetic, have also been employed in biological testing with vast range of activities, such as antibmicrobial, [12][13][14][15] antiinflamatory, 16 antioxidant, [17][18][19][20][21] anticancer, 17,19,20 larvicidal, 22,23 antihelmintic, 24,25 also acting as enzyme inhibitors (acetylcholinesterase and butyrylcholinesterase, 26 mushroom tyrosinase, 27 Mycobacterium tuberculosis chorismate mutase 28 ).…”
Section: Introductionmentioning
confidence: 99%